Comprehensive assessment of the probability and severity of accidents at the mines of Donskoy gok using the Kinney method (Международный научный журнал «Инженер», 2026)
The article examines an approach to the comprehensive assessment of occupational injury risks in theunderground mining operations of the Donskoy Mining and Processing Plant using the Kinney method. Theanalysis is based on data from 180 registered accidents that occurred over a 21-year period at the“Molodezhnaya,” “DNK,” and “ShSC” mines. Hazard identification was carried out using an internal classifier,highlighting the most significant events, including rock falls and collapses, the impact of moving machinery,and falls from heights. Calculations using the Kinney method showed that the risk level for the main hazard type(code 15) exceeds acceptable thresholds (R = 300, with a permissible limit of 70 points), classifying it as anunacceptable risk. Reasoned conclusions were made regarding the necessity of implementing preventivemeasures based on quantitative analysis. The proposed approach allows for the systematization of industrialsafety management at facilities with a high level of injury risk.